2008
DOI: 10.1111/j.1742-4658.2008.06753.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of kinase activity in Mycobacterium tuberculosis multidomain protein Rv1364c

Abstract: The alternative sigma factors are regulated by a phosphorylation‐mediated signal transduction cascade involving anti‐sigma factors and anti‐anti‐sigma factors. The proteins regulating Mycobacterium tuberculosis sigma factor F (SigF), anti‐SigF and anti‐anti‐SigF have been identified, but the factors catalyzing phosphorylation–dephosphorylation have not been well established. We identified a distinct pathogenic species‐specific multidomain protein, Rv1364c, in which the components of the entire signal transduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 49 publications
6
29
2
Order By: Relevance
“…The full-length Rv1364c protein showed pNPP hydrolysis activity in vitro, consistent with previous results (18). In addition, we found that fusion to the RsbT domain activated the phosphatase domain ϳ18-fold (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The full-length Rv1364c protein showed pNPP hydrolysis activity in vitro, consistent with previous results (18). In addition, we found that fusion to the RsbT domain activated the phosphatase domain ϳ18-fold (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…We found that Rv1364c encodes an active phosphatase that is stimulated by the anti-sigma factor domain. Moreover, contrary to a recent report (18), the anti-sigma factor domain functions as an active kinase. Mutational inactivation of the phosphatase catalytic site stabilized phosphorylated Rv1364c, while mutations of the kinase active site or the predicted phospho-acceptor residue blocked phosphorylation.…”
contrasting
confidence: 97%
See 3 more Smart Citations